ANALISIS PENGENDALIAN KUALITAS MENGGUNAKAN METODE SIX SIGMA UNTUK MEMINIMASI CACAT PRODUK PADA PT. BUMIPUTRA MANUFAKTUR TEKNOLOGI - yola yolia sari; resista vikaliana (Prosiding Seminar Nasional Manajemen Industri dan Rantai Pasok, 2021)
ABSTRACT The purpose of this study was to determine product quality control by PT Bumiputra Manufaktur Teknologi. The research method used was a descriptive qualitative approach. Informants were employees of the Die Casting Department of PT Bumiputra Manufaktur Teknologi. From the selection based on the purposive sampling method, 3 informants were obtained. The data used in this study were primary data. Data was collected through observation, interviews, and documentation. This study used the Six Sigma (DMAIC) method. The results showed that the Crank Case Comp production process during the period of January-April 2021 resulted in 2519 pcs of product defects, with chipping as the highest type of defect, namely 34%, followed by porous defect (29%), bending defect (21%), and scratch defect (16%). Based on the sigma calculation, the DPMO value is 5100, while the sigma value obtained by PT Bumiputra Manufaktur Teknologi is 4.07. Kata Kunci : Pengendalian Kualitas, Six Sigma, DMAIC